2020
DOI: 10.24042/tadris.v5i1.6153
|View full text |Cite
|
Sign up to set email alerts
|

Student’s Responses on Learning in the Early COVID-19 Pandemic

Abstract: The coronavirus disease (COVID-19) pandemic forced many universities to apply online learning. The purpose of this study was to break down the online learning process in the early pandemic as well as effective and optimal online learning. The design of this research is descriptive qualitative research. The data were collected through observation, questionnaires, interviews, and documentation. Interestingly, this study found online learning using the WhatsApp Group to be the most effective in the early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
0
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(200 citation statements)
references
References 22 publications
(25 reference statements)
6
124
0
19
Order By: Relevance
“…Faculty training to support this transition—as well as student engagement and connectedness—has been identified as crucial to its success (Barr and Miller 2013 ). Whilst the use of already-familiar applications, such as WhatsApp, proved useful for remote-learning during the early pandemic (mid-March), research has highlighted the need for more effective practices for the post-emergency stage (Wargadinata et al 2020 ). However, due to the sudden emergence of Covid-19, most faculty members faced unforeseen challenges, including lack of online-teaching experience, lack of time for preparing distance-learning courses, and figuring out how to make use of support from educational technology teams (Bao 2020 ).…”
mentioning
confidence: 99%
“…Faculty training to support this transition—as well as student engagement and connectedness—has been identified as crucial to its success (Barr and Miller 2013 ). Whilst the use of already-familiar applications, such as WhatsApp, proved useful for remote-learning during the early pandemic (mid-March), research has highlighted the need for more effective practices for the post-emergency stage (Wargadinata et al 2020 ). However, due to the sudden emergence of Covid-19, most faculty members faced unforeseen challenges, including lack of online-teaching experience, lack of time for preparing distance-learning courses, and figuring out how to make use of support from educational technology teams (Bao 2020 ).…”
mentioning
confidence: 99%
“…Instructors could also place links and 'information bits' on course pages to bring awareness to these services so that students are informed about the range of support services. Furthermore, supported by findings of this study and those of [12,19], it is strongly recommended that prior to the start of their courses, students complete an ELS orientation inclusive of an e-readiness assessment, even if it is a self-evaluation. This assessment, also supported by [21,22], would provide an initial baseline and also highlight any e-readiness deficiencies that require additional support or ELS training.…”
Section: Author Detailsmentioning
confidence: 54%
“…Electronic learning (e-learning) is defined as the use of technology (e.g., computer or electronic device) to provide learning material including tutorials, simulations, case-or game-based learning modules [19]. It is a system that promotes online learning by storing, processing, and distributing teaching materials.…”
Section: E-learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies conducted at the beginning of the covid-19 pandemic found WhatsApp Group the most influential media used for learning (Suni Astini, 2020;Wargadinata et al, 2020). WhatsApp Group was still apparent as teachers' common choice in the present study, yet it had more commonly been employed in a combination of two or more other learning applications.…”
Section: Students Experience In Learning English Onlinementioning
confidence: 60%